2013
DOI: 10.1002/jemt.22231
|View full text |Cite
|
Sign up to set email alerts
|

A place for ultrastructural analysis of platelets in cerebral ischemic research

Abstract: It is well known that estrogen is neuroprotective through various mechanisms which suggest that sex hormone levels, thrombotic mechanisms, and inflammatory processes are strongly interconnected in predicting the outcome and consequences of cerebral ischemia. Because platelet ultrastructure is altered in conditions like thrombosis and associated with stroke, the question arises whether ultrastructural analyses of platelet morphology may provide further insight into the role of estrogen during ischemic insult. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…One of the hallmarks of inflammation is a pathological coagulation system, and this is the direct result of upregulated circulating inflammatory molecules. During inflammation, platelets become aggregated and activated, with microparticle formation; RBCs become eryptotic and also produce microparticles (Van Der Spuy & Pretorius, ; Gasparyan et al , ; Pretorius & Kell, ; Bester & Pretorius, ; Pretorius et al , ,c; Soma et al , ); and pathological plasma clots form, mainly due to pathological changes in the healthy fibrin(ogen) protein structure (Kell & Pretorius, ; Pretorius et al , ). Therefore, by studying the effect of individual inflammatory molecules on RBCs, platelets and fibrin(ogen) we may improve our understanding of the inflammatory response and provide important advances in understanding both inflammation regulation and the resulting pathophysiological coagulation.…”
mentioning
confidence: 99%
“…One of the hallmarks of inflammation is a pathological coagulation system, and this is the direct result of upregulated circulating inflammatory molecules. During inflammation, platelets become aggregated and activated, with microparticle formation; RBCs become eryptotic and also produce microparticles (Van Der Spuy & Pretorius, ; Gasparyan et al , ; Pretorius & Kell, ; Bester & Pretorius, ; Pretorius et al , ,c; Soma et al , ); and pathological plasma clots form, mainly due to pathological changes in the healthy fibrin(ogen) protein structure (Kell & Pretorius, ; Pretorius et al , ). Therefore, by studying the effect of individual inflammatory molecules on RBCs, platelets and fibrin(ogen) we may improve our understanding of the inflammatory response and provide important advances in understanding both inflammation regulation and the resulting pathophysiological coagulation.…”
mentioning
confidence: 99%
“…27 Platelets aggregate with leukocytes in areas of ischemia/reperfusion injury. 29 The activated platelets interact with and signal to other inflammatory cells, such as leukocytes, and release their granules in high concentrations. Between 0.26 and 7.6% of HIV-infected patients will have venous thromboembolism (VTE) and activated platelets have been suggested as the etiology.…”
Section: Circulating Inflammatory Markers and Their Effects On The Hementioning
confidence: 99%
“…In their groups, it was found that male (NTI = 23.897%) rats displayed significantly more neural tissue injury than acyclic females (NTI = 13.466%) who also in turn displayed significantly more neural tissue injury than cyclic females (NTI = 9.217%) (Figure 4). Previously, neural tissue injury of this subset of animals was correlated to alterations in platelet ultrastructure at specific time points to establish that neural injury and the fluctuation of inflammation associated with such injury is mirrored by changes in platelet morphology [15].…”
Section: Neural Tissue Injury Was Higher In Males Than Cyclic or Acycmentioning
confidence: 99%
“…From the neural tissue injury results, it can be deduced that subsequent to cerebral ischemia cyclic female neural tissue presents the lowest overall loss of integrity with high estradiol levels curbing inflammation early on [15] and initiating recovery by stalling apoptosis [22,23]. The neural tissue of males is shown to deteriorate significantly in the absence of adequate estradiol due to an inability to curb the inflammatory response and suppress apoptosis.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation